FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI KELURAHAN CAMPAGO IPUH KOTA BUKITTINGGI TAHUN 2018 - HARISNAL, HARISNAL (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Dengue Hemorrhagic Fever (DHF) is caused by dengue virus transmitted by Aedes Aegypti mosquitoes. Based on data from the Bukittinggi City Health Office (DKK) in 2017 as many as 90 cases. This study aims to determine the factors associated with the incidence of Dengue Hemorrhagic Fever (DHF) in Campago Ipuh Village, Bukittinggi City in 2018. The type of research used is descriptive analytic with cross sectional design. This research was carried out by all families in Campago Ipuh Village in 2018 totaling 2636 households, the sample was taken systematically random sampling totaling 99 families. By using the chi squere test with a confidence level (CI) 95% (<0.005). The results of univariate analysis (66.7%) had low knowledge, (71.7%) respondents had a negative attitude, (63.6%) respondents who did not carry out the act of Eradicating Mosquito Nests (PSN), (62.6%) respondents who assume that the role of the officer is less active. Bivariate results showed a significant relationship between knowledge with the incidence of DHF (p = 0.007 and OR = 3.61), attitudes with DHF incidence (p = 0.020 and OR = 3.17), PSN actions with DHF incidence (p = 0.002 and OR = 4.11), the role of officers with dengue incidence (p = 0,000 and OR = 0,115). It was concluded that related to the incidence of DHF were knowledge, attitudes, actions of PSN, the role of officers. It is suggested to the public to be more active in the PSN action to avoid the incidence of DHF. Keywords: Dengue Hemorrhagic Fever (DHF), Knowledge, Attitude, PSN Actions, Role of Officers Reference: 23 (2005-2017)